PENGARUH GAYA KEPEMIMPINAN DEMOKRATIS, KOMITMEN ORGANISASI DAN INTEGRITAS TERHADAP KINERJA AUDITOR PADA PERWAKILAN BADAN PENGAWASAN KEUANGAN DAN PEMBANGUNAN (BPKP) PROVINSI KALIMANTAN SELATAN - M. Riduan Abdillah; Hasnan Ash-Shiddieqy; Gusti Azizussalam (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2019)
Abstrack This research aims to find empirical evidence that democratic leadership style, organizational commitment and integrity influence the performance of auditors in the Representatives of the Financial and Development Supervisory Agency (BPKP) of South Kalimantan Province. This research method is a quantitative method. The population of this study was the BPKP South Kalimantan BPKP Representative numbering 90 people. The determination of the sample of this study uses saturated samples. Data analysis using multiple linear regression with a significance level of 5% The results of this research find empirical evidence that democratic leadership style does not partially affect auditor performance, organizational commitment partially affects auditor performance and integrity does not partially affect auditor performance.